An Experimental Investigation of Reaeration and Energy Dissipation in Hydraulic Jump - Kucukali, Serhat; Cokgor, Sevket (Springer International Publishing, 2020)
A hydraulic jump is characterized by a highly turbulent flow with macro-scale vortices and some kinetic energy dissipation. Reaeration is defined as the transfer of oxygen from air towards water. Aeration performance of a classical hydraulic jump has been investigated by means of energy dissipation in a 0.5 m wide flume with upstream Froude and Reynolds numbers ranging from 2.3 to 6.4 and 1.4 to 5.4 × 104, respectively. Dissolved Oxygen (DO) measurements were conducted simultaneously upstream and downstream of the hydraulic jump with a manual oxygen meters. A strong correlation was found between the reaeration and energy dissipation rate indicating the macro turbulence dominant role in the process. In addition, the turbulence quantities were collected by an Acoustic Doppler Velocimeter (ADV) at low Froude numbers. Turbulent kinetic energy and Reynolds shear stress took their maximum values at the toe of the jump and exhibited a longitudinal decay. We related macro-scale turbulent length scale with upstream flow depth. The average energy dissipation rate has been correlated with the 1.5 power of the maximum turbulent kinetic energy in a dimensionally homogeneous form.